The Influence of Tik-Tok Social Media, Celebrity Endorsers and Product Quality on Bittersweet By Najla Consumer Purchasing Decision (Study On Bittersweet By Najla Consumers at Malang Raya) - Rofiqoh Abidah; Muslikhati; Sri Cahyaning Umi Salama (Universitas Darussalam Gontor, 2024)
This research aims to determine the influence of Tik-Tok social media,Celebrity Endorser and Product Quality on Bittersweet Product Purchasing Decisions By Najla. The method used is quantitative with an associative approach, using 127 samples, from Greater Malang area including Batu City, Malang City and Malang Regency. This research used analytical methods Structural Equation Model (SEM) with software smart partial least square (PLS) 4.0. The results of this research show that (1) Tik-Tok social media has a significant influence on purchase decision for Bittersweet's By Najla; (2) Celebrity Endorser significant influence on purchase decision for Bittersweet's By Najla; and (3) Product quality has an significant effect on the decision to purchase Bittersweet By Najla Keywords: Tik-Tok Social Media, Celebrity Endorser, Product Quality, Purchase Decisions.